Regulating, Supervising, and Handling Distress in Public Banks - Adams, Mark.; Aydin, Hanife; Chon, Hee.; Morozova, Anastasiia (Washington, D.C. : International Monetary Fund, 2022)
This paper highlights the distinct challenges and suggests practical solutions to the effective regulation, supervision, and crisis management for public banks. It acknowledges that public banks exist for variety of reasons (legacy, ideology, public policy) and will likely remain a feature of financial systems in a number of countries. On this basis, it provides advice on how to best incorporate public banks in the regulatory paradigm commensurate with their risk profiles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Crises; General Financial Markets; Micro Finance Institutions